Cost-Effectiveness of Pembrolizumab Plus Chemotherapy as First-Line Therapy for Advanced Oesophageal Cancer - Wu, Meiyu; Qin, Shuxia; Wang, Liting; Tan, Chongqing; Peng, Ye; Zeng, Xiaohui; Luo, Xia; Yi, Lidan; Wan, Xiaomin (Frontiers in Pharmacology, 2022)
Objective: Pembrolizumab plus chemotherapy is recommended as the first-line treatment for advanced oesophageal cancer. The objective of this study is to evaluate the cost-effectiveness of pembrolizumab plus chemotherapy as first-line therapy for advanced oesophageal cancer from the healthcare system perspective in China. Methods: Based on the KEYNOTE-590 trial, a Markov model was constructed to estimate the cost and effectiveness of pembrolizumab plus chemotherapy and placebo plus chemotherapy, respectively. Total costs, life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were calculated. One-way, probabilistic sensitivity analyses (PSA), subgroup analyses were adapted to test the model robustness. Result: Compared with the placebo group, pembrolizumab group obtained an additional 1.05 QALY, but the cost was also increased by $121,478.76. The ICER was $115,391.84 per QALY gained, which was higher than the willingness-to-pay (WTP) of $31304.31. The results of One-way sensitivity analyses showed that the result was sensitive to the hazard ratio of PFS and per cycle cost of pembrolizumab. At a WTP threshold of $31304.31, the probability of pembrolizumab plus chemotherapy being cost-effective was 0%. Conclusion: From the perspective of China healthcare system, pembrolizumab plus chemotherapy as first-line treatment is not cost-effective for patients with advanced oesophageal cancer compared with placebo plus chemotherapy.